Analysis of Digital Literacy of MIPA and MIPA Education Students - Djarwo, Catur Fathonah; Paul Johan Kawatu; Fridolin Nadap Yokhu; Nadila Meylani Kirey Putri (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
UNCEN Mathematics and Natural Sciences Education Department students are students who actively play a role in utilizing digital information sources. However, this raises problems regarding the use of digital sources. So because of the problems that often occur, it is not yet known whether students have utilized digital resources properly and correctly, so research needs to be conducted to find out more about what the digital literacy of students majoring in Mathematics and Natural Sciences Education is like in supporting learning using instant DCA (Digital Competence Assessment) measurements. which is a model and instrument used to determine and measure a person's digital literacy abilities. The research results show that the digital literacy skills of students majoring in P.MIPA in using technology are in the sufficient category with a percentage achievement of 59.25%. In the cognitive dimension, the overall percentage of results was 54.92%, which was categorized as sufficient. Meanwhile, in the ethical dimension, the overall percentage of results was 62.76%, which is categorized as good